The Influence of Job Stress Mediates Work-Family Conflict on Employee Job Satisfaction - Annisa, Nenden Nur; Wardhani, Diana Pramudya; Verawati, Liesta (Jurnal Manajemen Dayasaing, 2024)
Employees are one of the important elements in achieving company goals, therefore, employees as an important source in the success of a company should be considered, especially regarding their satisfaction at work or what is commonly known as job satisfaction. The objectives of this study are (1) Testing the effect of work-family conflict on job satisfaction in employees (2) Testing the effect of work-family conflict on job stress in employees. (3) Testing the effect of job stress on job satisfaction in employees. (4) Testing job stress in mediating the effect of work- family conflict on job satisfaction in employees. The population in this study were 119 employees. Sampling using purposive sampling method using criteria in the study amounted to 80 people. The data collection instrument uses a questionnaire with a Likert scale, each of which has been tested and has met the validity and reliability requirements. Data analysis using SmartPLS 3.0 tools. The results of this study indicate that (1) Work-family conflict has a negative and significant effect on job satisfaction in employees. (2) Work-family conflict has a positive and significant effect on job stress in employees. (3) Job stress has a negative and significant effect on job satisfaction in employees (4) Job stress mediates the effect of workfamily conflict on job satisfaction in employees.